Combined effects of thin-section size, grain size and cavities on the high temperature creep fracture properties of a nickel-base superalloy - Baldan, A (Chapman Hall Ltd, 1997)
The creep fracture characteristics of a conventionally cast (CC) MAR-M 002 superalloy, controlled by the grain-boundary diffusion mechanism, have been investigated at various specimen section-sizes D, and grain sizes, d. It is observed that the creep rupture strain (or ductility), epsilon(R), is controlled by the D-2/(n(G)/) ratio, where n(G) is the number of grains per cross-section of specimen and / is the half-cavity spacing, at the creep conditions (900 degrees C/300 MPa). A rapid improvement in creep rupture life can be made by reducing the (d(C)/d)/D ratio [or, equivalently, the (d(C)n(G))/D-2 ratio] below a critical value (similar to 100 x 10(-8) mu m(-1)), where d(C) is the cavity size. The thin-section size dependent creep rupture life, t(R)/D, and creep rupture strain, epsilon(R)/D, are explained on the basis of grain boundary sliding (GBS) and creep crack growth (CCG) behaviour of the alloy. epsilon(R)/D and t(R)/D can be improved by reducing the GBS rate. A large improvement in t(R)/D can be achieved by reducing the GBS and CCG rates below the critical values of these rates by reducing the crack size through increasing the grain size above a critical value. (Above a critical grain size value the crack size becomes so small that, as a result, a large increment of t(R) is achieved.)
Keywords: Boundaries